Developing Novel Therapies for Degenerative Cervical Myelopathy [AO Spine RECODE-DCM Research Priority Number 7]: Opportunities From Restorative Neurobiology. Issue 1 (February 2022) - Gharooni, Aref-Ali; Kwon, Brian K.; Fehlings, Michael G.; Boerger, Timothy F.; Rodrigues-Pinto, Ricardo; Koljonen, Paul Aarne; Kurpad, Shekar N.; Harrop, James S.; Aarabi, Bizhan; Rahimi-Movaghar, Vafa; Wilson, Jefferson R.; Davies, Benjamin M.; et al.
Study design: Narrative review. Objectives: To provide an overview of contemporary therapies for the James Lind Alliance priority setting partnership for degenerative cervical myelopathy (DCM) question: 'Can novel therapies, including stem-cell, gene, pharmacological and neuroprotective therapies, be identified to improve the health and wellbeing of people living with DCM and slow down disease progression?' Methods: A review of the literature was conducted to outline the pathophysiology of DCM and present contemporary therapies that may hold therapeutic value in 3 broad categories of neuroprotection, neuroregeneration, and neuromodulation. Results: Chronic spinal cord compression leads to ischaemia, neuroinflammation, demyelination, and neuronal loss. Surgical intervention may halt progression and improve symptoms, though the majority do not make a full recovery leading to lifelong disability. Neuroprotective agents disrupt deleterious secondary injury pathways, and one agent, Riluzole, has undergone Phase-III investigation in DCM. Although it did not show efficacy on the primary outcome modified Japanese Orthopaedic Association scale, it showed promising results in pain reduction. Regenerative approaches are in the early stage, with one agent, Ibudilast, currently in a phase-III investigation. Neuromodulation approaches aim to therapeutically alter the state of spinal cord excitation by electrical stimulation with a variety of approaches. Case studies using electrical neuromuscular and spinal cord stimulation have shown positive therapeutic utility. Conclusion: There is limited research into interventions in the 3 broad areas of neuroprotection, neuroregeneration, and neuromodulation for DCM. Contemporary and novel therapies for DCM are now a top 10 priority, and whilst research in these areas is limited in DCM, it is hoped that this review will encourage research into this priority.